Thermodynamically primed Atmospheric River Rapid as the driver of the December 2023 Thoothukudi extreme rainfall - Sivachitralakshmi, S.; Chitra, P. (Frontiers in Climate, 2026)
The December 2023 extreme rainfall over Thoothukudi, India (946 mm in 24 h), represents a pronounced precipitation efficiency anomaly, as such intensity occurred in the absence of a synoptic-scale cyclonic storm and exceeded rates explainable by resolved large-scale ascent. This study introduces a newly proposed Atmospheric River Rapid Index (ARRI) to diagnostically examine whether this event is consistent with the influence of a thermodynamically primed tropical Atmospheric River Rapid (AR Rapid). Using GPM IMERG precipitation estimates and ERA5 reanalysis, we apply a diagnostic Eulerian moisture budget decomposition to assess the processes contributing to the event. The analysis indicates a dual influence: the large-scale environment was thermodynamically primed by background moisture anomalies (dynamic term ≈ 33.0%), while the spatial concentration and intensity of rainfall are primarily associated with anomalous wind steering and convergence of integrated vapor transport (thermodynamic circulation term ≈ 102.0%) within a vector framework. The ARRI identifies a narrow coastal region characterized by peak IVT, strong IVT convergence, deep moisture, and reduced low-level wind speeds, consistent with frictional deceleration of a low-level jet at landfall and consistent with conditions favorable for AR Rapid ascent. Complementary dynamical diagnostics further suggest a limited contribution from organized synoptic-scale cyclonic mechanisms. These results provide diagnostic evidence consistent with a thermodynamically primed AR Rapid suggesting a key contributing process to this extreme, non-cyclonic tropical rainfall event. The findings highlight limitations of cyclone-centric forecasting approaches and underscore the potential value of monitoring IVT convergence and thermodynamic pre-conditioning for anticipating high-impact tropical flood events.